Sub- State Diplomacy as to Contemporary Indonesian Diplomacy: Paradiplomacy strategy in strengthening sister city cooperation in tourism sector - Fathun, Laode Muhamad; Suadhana Rai, I Nyoman Aji; Nathania, Vania Zahra; Wahidah, Tuhfahtu Hasanatul (LP2M, 2024)
This research aims to explain Indonesian sub-state diplomacy as a style of contemporary Indonesian diplomacy to achieve national interests. Currently, national interests are not only carried out in a monopolistic manner by the state. However, sub-state actors are also involved as actors who support Indonesian diplomacy in the contemporary era. This article uses a qualitative methodology based on case studies. This research uses data collection techniques of observation, interviews and literature. This research shows that cooperation between regions, namely Australia represented by New South Wales and Indonesia represented by DKI Jakarta, has the potential for good cooperation. This is based on the excellent relations between the two countries plus sister city cooperation between the two capital regions to support the implementation of cooperation. The cooperation carried out in the tourism sector is a collaboration between two regions which is very profitable in the tourism economic sector. Because both regions are areas that have the same character, namely maritime areas. This cooperation must be based on collaboration at the country level using the joint comparative foreign policy method. This means that the regional government supports national cooperation which is implemented in the form of sister city cooperation.